1972
DOI: 10.1002/art.1780150404
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis as the presenting feature of childhood leukemia

Abstract: Five cases of childhood leukemia are described in which major presentation was arthritis. Three patients had normal hematologic studies when initially examined. Both monoarticular and polyarticular arthritis were seen. Joint swelling was caused by an increase in synovial fluid, but in 1 patient there seemed to be synovial thickening. Presentations and clinical courses were extremely variable and point out the necessity to consider leukemia in the differential diagnosis of children with arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 7 publications
1
21
0
3
Order By: Relevance
“…2,3 Several studies concerning the musculoskeletal manifestations of childhood leukemias have shown the importance of these complaints in the clinical presentation and follow-up of these patients. 1,[4][5][6][7][8][9][10] The aims of the present study were to determine retrospectively the frequency and type of occult neoplasias in children who initially presented with musculoskeletal complaints, as well as determining the clinical features and laboratory alterations that can suggest such malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several studies concerning the musculoskeletal manifestations of childhood leukemias have shown the importance of these complaints in the clinical presentation and follow-up of these patients. 1,[4][5][6][7][8][9][10] The aims of the present study were to determine retrospectively the frequency and type of occult neoplasias in children who initially presented with musculoskeletal complaints, as well as determining the clinical features and laboratory alterations that can suggest such malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Bu bulgular nonspesifik olup, ateş yüksekliği, hâlsizlik, solukluk, ekstremite ve eklem ağrılarıdır (1) . ALL ço-cuklarda kemik ve ekstremite ağrılarından çok tek veya çoklu eklem tutulumu ile seyretmektedir (8,9) . Olgumuz da üç yaşında erkek hasta olup, sağ dirsek eklemi ağrısı nedeniyle başvurmuştu.…”
Section: Discussionunclassified
“…Há vários trabalhos na literatura que observaram a freqüência e características deste tipo de manifestação inicial nas doenças linfoproliferativas 7,8,15,16 . No nosso estudo, ocorreram em 62% dos casos, semelhante ao apresentado na literatura estudada.…”
Section: Discussionunclassified
“…Alguns trabalhos têm descrito as manifestações reumatológicas das leucemias, uma vez que queixas músculo-esqueléticas podem ser sua manifestação inicial 7,[12][13][14][15][16] . A artrite em leucemias pode ser crônica ou recorrente, e geralmente apresenta-se de forma pauciarticular assimétri-ca, geralmente aditiva, mas pode ser também migratória e seu início pode ser súbito ou insidioso 6 .…”
Section: Introductionunclassified